Explore the Meaning of the Legal System in the Framework of Developing Legal Science and National Legal System - Abdul Ghofur Anshori (Fakultas Hukum, Universitas Warmadewa, 2023)
Even though the legal system is open, the existence of three legal systems in the Indonesian legal system is felt to be an obstacle in determining the right legal system for Indonesia. People still think that in Indonesia, customary, Islamic and Western laws apply as a system, whereas in fact the three legal systems are in one system. The Indonesian legal system is extracted from the local wisdom and local genius of the Indonesian nation without turning a blind eye to changes in the international world. Western law, especially the Anglo Saxon system, customary law and Islamic law can each become raw material in national law. There is no need to contradict the three, but we can synergize them in national law as one Indonesian legal system. The archipelago has a diversity of ethnic groups with diverse social institutions and forms a single unit (Bhinneka Tunggal Ika). The Indonesian legal system certainly has to pay attention to this. For the Indonesian nation, the formation of a national society composed of social subsystems called ethnic groups, and each ethnic group has a system of norms adopted by each ethnic group, is often referred to as customary law. The Indonesian legal system has a metaphysical essence originating from the Indonesian nation itself so that the system is inherent in the Indonesian nation. The essence of metaphysics becomes the foundation and directs law. The metaphysical essence is the values contained in Pancasila and the 1945 Constitution.